Big Data for the Greater Good - Emrouznejad, Ali.; Charles, Vincent; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book highlights some of the most fascinating current uses, thought-provoking changes, and biggest challenges that Big Data means for our society. The explosive growth of data and advances in Big Data analytics have created a new frontier for innovation, competition, productivity, and well-being in almost every sector of our society, as well as a source of immense economic and societal value. From the derivation of customer feedback-based insights to fraud detection and preserving privacy; better medical treatments; agriculture and food management; and establishing low-voltage networks - many innovations for the greater good can stem from Big Data. Given the insights it provides, this book will be of interest to both researchers in the field of Big Data, and practitioners from various fields who intend to apply Big Data technologies to improve their strategic and operational decision-making processes.
Big Data for the Greater Good: An Introduction -- Big Data Analytics and Ethnography: Together for the Greater Good -- Big Data: A Global Overview -- Big data for predictive analytics in high acuity health settings -- A Novel Big Data-Enabled Approach Individualizing and Optimizing Brain Disorder Rehabilitation -- Big Data in Agricultural and Food Research: Challenges and Opportunities of an integrated Big Data e-Infrastructure -- Green neighbourhoods: the role of big data in low voltage networks' planning -- Big Data Improves Visitor Experience at Local, State, and National Parks - Natural Language Processing Applied to Customer Feedback -- Big Data and Sensitive Data.
Keywords: Computational intelligence; Quantitative research; Artificial intelligence; Computational Intelligence; Data Analysis and Big Data; Artificial Intelligence